Desain Desain Sistem Informasi Rekam Medis dalam Menunjang Pelaporan Keluarga Berencana (KB) di RSIA Limijati dengan Metode Agile - Sheevie Tsaqifa; Syahidin, Yuda; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The main problem faced today is the lack of structure in the reporting of family planning measures at RSAI Limijati. Reporting does not distinguish the type of family planning performed by the patient and does not provide information on whether the patient is performing a new family planning procedure or repeating the previous one. As a result, the resulting report is not well structured and does not provide a clear picture of patient data according to the type of family planning and the history of family planning actions that have been taken. To overcome this problem, this study proposes a qualitative approach with a descriptive approach developed using the agile method. This method aims to develop a medical record information system that is able to produce a well-structured final report for each patient's data, taking into account the type of birth control performed. The system will also provide a detailed explanation of whether the patient is taking a new family planning procedure or repeating the previous one, and will record this information along with other patient data such as demographic data and medical history. The result of applying this method is expected to produce a more structured and informative family planning reporting system. This improved system will make it easier to conduct family planning reporting and ensure that patient data is well organized. Information on family planning measures for each patient can also be obtained more easily according to the type of family planning performed, providing a more complete and accurate picture of the patient's condition related to family planning.